Pengembangan E-Modul Interaktif Flipbook Untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD Pada Materi Gaya Di Sekitar Kita - Simamora, Ebeneser Wacner; Siregar, Nahrun Najib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: (1) determine the validity of the interactive flipbook e-module on the material of forces around us; (2) determine the practicality of the interactive flipbook e-module on the material of forces around us; (3) determine the effectiveness of the interactive flipbook e-module on the material of forces around us. The type of research used in this study is research and development (Research and Development). In this study, the ADDIE research method was used, namely Analysis, Design, Development, Implementation, Evaluation. The subjects of this study were fourth-grade students of SD Inpres 09 Anggori. The data for this study were obtained through interviews, observations and questionnaires. The instruments used in data collection consisted of a validation sheet to measure validity, a student response questionnaire to measure practicality and test items to measure effectiveness. The overall average result of validation of the interactive flipbook-based heyzine e-module was 3.74, and was in the very valid category. The practicality of the flipbook-based interactive e-module demonstrated that the average total score obtained by students was 3.83, which is considered very positive. The average student test score was 82.4. The percentage of student learning outcomes showed that 88% of students achieved a passing grade (22 students).